MEDIA MANIPULATION BASED ON THE LINGUISTIC FEATURES OF THE INTERNET SPACE (TAMADDUN NURI JURNALI, 2025)
The subject of this study was the linguistic features of information transmission, allowing for mediaconvergence in servicing the communication of the Internet information field.